PEMBUATAN BIODIESEL DARI MINYAK BIJI KAPOK DENGAN PROSES ESTERIFIKASI TRANSESTERIFIKASI - Nixon Poltak Frederic; H. Diyono Ikhsan (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
The application of kapok seed oil, directly for diesel fuel is still facing a problem. The problem is mainlydue to the kapok seed oil has very high viscosity compared with petroleum diesel. To solve that problem weneed to convert the kapok seed oil into methyl ester by esterification transesterification reaction withcatalyst. Steps being taken to obtain the methyl esters by reaction of kapok seed oil and methanol catalyzedby KOH with the addition of methanol variation of 70 ml, 80 ml, 90 ml, 100 ml, 110 ml in the first reaction(esterification) and the second reaction (transesterification) of 50 ml, 40 ml, 30 ml, 20 ml, 10 ml. Then itsvariable temperature of 40 0C, 50 0C, 50 0C, 60 0C, 70 0C, 80 0C in the first reaction (esterification), and thetemperature of the room on the second reaction (transesterification). And in its time variable 30 minutes, 45minutes, 60 minutes, 60 minutes, 75 minutes, 90 minutes in the second reaction. From the results of ourcalculations, the highest biodiesel conversion in the esterification reaction (Trans I) reached 93.95% at areaction time of 90 minutes, the amount of 110ml methanol and the reaction temperature of 80 0C. Thenproceed with the process of transesterification (Trans II) at a temperature of 30 0C, obtained the highestconversion of 97.22%, the reaction time of 90 minutes and the amount of 50ml methanol. And already meetsthe biodiesel specification according to ISO-04-7182-2006 conversion of the resulting biodiesel is aminimum of 96.5%. From this study it can be concluded, esterification process kapok kapok seed oiltransesterification able to produce biodiesel, the greater the reaction temperature the conversion of theresulting ester is greater.